IMPLEMENTASI PHT: PENGGUNAAN AGENS BIOLOGIS BURUNG HANTU PUTIH UNTUK PENGENDALIAN HAMA TIKUS DI DESA PULOMULYA KECAMATAN LEMAHABANG KABUPATEN KARAWANG - Afifah, Lutfi; Nurcahyo W. Saputro; Ultach Enri (Jurnal Abditani, 2024)
The rat pest Rattus argentiventer is a severe problem in Karawang, it harms by damaging rice plants. Farmers do not have enough knowledge about how to deal with the pest. The partners in this activity are the Pulomulya Village Farmer Group, Lemahabang, with approximately 30 members. This community service provides knowledge about natural enemy conservation through planting refugia plants that can attract natural enemies and become a shelter for predators and parasitoids. As a result, farmers are able to conserve natural enemies by planting refugia around rice fields, and farmers are able to make artificial barn owl nests (rubuha) to control rat pests as an effort to implement Biointensive IPM. Farmer groups and communities have learned how to make rubuha and the required tools and materials. After the installation of the rubuha, Tyto alba barn owls came naturally and nested inside. This service allows farmers to use the biological agent Tyto alba and reduce the impact of using synthetic pesticides. With the successful use of these rubuha, the local government provided funding for a program to install 15 rubuha in 2023. The more rubuha installed, the better the natural rat control in Pulomulya Village. This innovation is an environmentally friendly solution to the rat problem in the area.